1994
DOI: 10.1007/bf00186168
|View full text |Cite
|
Sign up to set email alerts
|

Airway dysfunction in patients with Parkinson's disease

Abstract: To investigate pulmonary function abnormalities in Parkinson's disease (PD), we obtained maximal inspiratory and expiratory flow-volume curves in 63 patients (59 under treatment) with different stages of the disease, not filtered for respiratory symptoms. PD severity was evaluated by the Unified PD Rating Scale, the Webster's scale, and Hoehn and Yahr staging. Patients with more severe PD had lower percentage forced vital capacity (FVC%), and peak inspiratory and expiratory flows. Those with fluctuations and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
5
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 19 publications
1
48
5
4
Order By: Relevance
“…Prior studies in smaller groups of PD patients had reported a 29% to 67% incidence of "sawtooth" morphology [6][7][8][9]. We found only a 3% incidence, undoubtedly related at least in part to differing methods of patient selection.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Prior studies in smaller groups of PD patients had reported a 29% to 67% incidence of "sawtooth" morphology [6][7][8][9]. We found only a 3% incidence, undoubtedly related at least in part to differing methods of patient selection.…”
Section: Discussioncontrasting
confidence: 55%
“…"Sawtooth" curves demonstrated a sawtooth shape during exhalation, typically after the PEFR ( Figure 1B). This pattern has been attributed to upper-airway obstruction [6][7][8][9]. "Low PEFR, reproducible" curves had a rounded peak but were consistently reproducible ( Figure 1C), as is typically seen in patients with neuromuscular weakness [6][7][8][9].…”
Section: Spirometry Morphology Analysesmentioning
confidence: 67%
See 3 more Smart Citations